Initiation timing effect of levothyroxine treatment on subclinical hypothyroidism in pregnancy. (3rd October 2018) - Zhao, Lijie; Jiang, Guojing; Tian, Xingfang; Zhang, Xiaoqin; Zhu, Ting; Chen, Beibei; Wang, Yongxiang; Ma, Qingliang
Abstract: The aim of this study is to estimate the timing impact on levothyroxine replacement among pregnant women with subclinical hypothyroidism (SCH). Ninety-eight pregnant women diagnosed as SCH in the first trimester were randomly divided into three groups: Group A, instantly initiated levothyroxine after diagnosis; Group B, administrated treatment in the second trimester, and Group C, received no prescription. Incidence of pregnancy complications and pregnancy outcomes were compared among three groups and subgroup analysis were performed stratified with TPO status in Group B. Group A exhibited lower rate of pregnancy complications (9.7%) and adverse outcome (3.2%) than Group B (41.9% and 32.3%) and Group C (64.5% and 38.7%). But the late initiation treatment group shared a comparable complication and maternal outcome with untreated women ( p = .075 and .596, respectively). After stratified with TPOAb status in Group B, TPOAb + women experienced a remarkable lower complication (14.2%) and adverse outcome rate (7.1%) compared with negative subjects (64.7% and 45%, respectively). Our data suggest that levothyroxine administrated in the first trimester was associated with decreased risk of adverse obstetric event. Additionally, pregnant women with TPOAb positive could also benefit from thyroid hormone therapy even initiated in the second trimester.